Mechanisms of dispersal and colonisation in a wind-borne cereal pest, the haplodiploid wheat curl mite - Alicja Laska; Anna Przychodzka; Ewa Puchalska; Mariusz Lewandowski; Kamila Karpicka-Ignatowska; Anna Skoracka (Scientific Reports, 2022)
Abstract Dispersal and colonisation determine the survival and success of organisms, and influence the structure and dynamics of communities and ecosystems in space and time. Both affect the gene flow between populations, ensuring sufficient level of genetic variation and improving adaptation abilities. In haplodiploids, such as Aceria tosichella (wheat curl mite, WCM), a population may be founded even by a single unfertilised female, so there is a risk of heterozygosity loss (i.e. founder effect). It may lead to adverse outcomes, such as inbreeding depression. Yet, the strength of the founder effect partly depends on the genetic variation of the parental population. WCM is an economically important pest with a great invasive potential, but its dispersal and colonisation mechanisms were poorly studied before. Therefore, here we assessed WCM dispersal and colonisation potential in relation to the genetic variation of the parental population. We checked whether this potential may be linked to specific pre-dispersal actions (e.g. mating before dispersal and collective behaviour). Our study confirms that dispersal strategies of WCM are not dependent on heterozygosity in the parental population, and the efficient dispersal of this species depends on collective movement of fertilised females.